Persistent Prothrombotic State in a Patient With Alström Syndrome - Nihit Shah, BMBS, BMedSci; Zeina Abu Orabi, MBBS; Adrian T. Warfield, MBChB; Richard Steeds, MA, MBBS; Peysh A. Patel, MA, MBBChir, PhD (JACC: Case Reports, 2024)
We present the case of a patient with Alström syndrome who was found to have evidence of a prothrombotic state on autopsy after sudden cardiac death. To the best of our knowledge, this case of persistent prothrombotic milieu is the first described in a patient with Alström syndrome.